Modeling the past archaeology, history, and dynamic networks - Terrell, John; Golitko, Mark; Dawson, Helen; Kissel, Marc (Berghahn, 2023)
"How do researchers use dynamic network analysis (DYNA) to explore, model, and try to understand the complex global history of our species? Reduced to bare bones, network analysis is a way of understanding the world around us--a way called relational thinking--that is liberating but challenging. Using this handbook, researchers learn to develop historical and archaeological research questions anchored in DYNA. Undergraduate and graduate students, as well as professional historians and archaeologists can consult on issues that range from hypothesis-driven research to critiquing dominant historical narratives, especially those that have tended ignore the diversity of the archaeological record"--
Keywords: Netzwerkanalyse -- Soziologie; Methodologie; Archäologie; Archaeology / Methodology; System analysis; Social sciences / Network analysis; Archaeology / Statistical methods